Removal of Ni(II), Pb(II), and Cu(II) from Industrial Wastewater by Using NF Membrane - Algureiri, Ahmed H.; Abdulmajeed, Yossor R. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
This article reviews the technical applicability of nanofiltration membrane process for the removal of nickel, lead, and copper ions from industrial wastewater. Synthetic industrial wastewater samples containing Ni(II), Pb(II), and Cu(II) ions at various concentrations (50, 100, 150 and 200 ppm), under different pressures (1, 2, 3 and 4 bar), temperatures (10, 20, 30 and 40 oC), pH (2, 3, 4, 5 and 5.5), and flow rates (1, 2, 3 and 4 L/hr), were prepared and subjected treated by NF systems in the laboratory. Suitable NF membrane was chosen after testing a number of NF membranes (University of Technology-Baghdad), in terms of production and removal. NF system was capable of removing more than (85%, 78%, and 66% for Ni(II), Pb(II), and Cu(II) ions respectively). The permeate flux for all H.M ions for were ranges between (14 to 62 L/m2.hr). The results showed that the NF membrane was capable of treating industrial wastewater with any concentration of heavy metals ions and reducing the ion concentration to about (15, 22, and 34 ppm) for Ni(II), Pb(II), and Cu(II) ions respectively. The low level of the heavy metals concentration in the permeate implies that water with good quality could be reclaimed for further reuse. The NF membrane is characterized by efficiently H.M. ions removal medium with high productivity and very low pressure up to 1 bar, which means very little cost for NF system.